Human resource development in Malaysia and Singapore - Ismail, Maimunah; Mohd Rasdi, Roziah (Routledge, 2016)
This chapter provides an overview of the relevance of HRD in Latin America. The historical, political, economic, institutional, social, and cultural context of HRD in the region will be presented with emphasis on Bolivia, Nicaragua, Costa Rica, Peru, Argentina, Colombia, Belize, and Mexico. The interface of enterprise and HRD in Latin America will also be examined and the general vocational and educational base for HRD will be explored and subsequently discussed. This chapter remains one story in the pluralistic discourse regarding HRD in Latin America. In conclusion, it has to be reiterated that the primary stakeholders and shareholders of HRD in Latin America are individual governments. Consequently, HRD in Latin America is about leaders and policy makers making conscious efforts to enhance HRD in any strategy, process, program, or activity intricately tied to the alleviation of poverty and hunger, access to quality education, access to quality health care, and gender and ethnic equality.